Pengaruh Kepuasan Pelanggan dan Pelayanan Terhadap Peningkatan Penjualan di PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket) - Ennisah Ennisah; Nur Augus Fahmi; Tika Indria (Journal of Innovative and Creativity, 2025)
The research analysis aims to determine whether customer satisfaction has a partial positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). Does service have a partial positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). Do customer satisfaction and service simultaneously have a positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). This study uses multiple linear regression. The sample research was conducted using the "Accedential Sampling" method, which is a sampling method by choosing who happens to be there/met. In sampling, this study uses the Zikmund formula so that the sample is 100 respondents. Primary data collection uses a questionnaire. The results of the study show that customer satisfaction has a partial positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). Service has a partial positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). Customer satisfaction and service simultaneously have a positive and significant effect on increasing sales at PT. Jaya Anugerah Eternal Success (Brastagi Supermarket).